2020
DOI: 10.1021/acsomega.9b03469
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Dew Point Measurement and Model Evaluation of Synthetic and Real Natural Gases

Abstract: Hydrocarbon dew point (HCDP) is one of the most important quality specifications of natural gas. Measuring and predicting the HCDP accurately are essential for the natural gas industry. However, the comprehensive experimental HCDP curve data are still rare, and knowledge about adopting proper prediction models remains unclear. In view of this, HCDP determination work by use of an improved test system and model evaluation based on more than 1000 dew points data have been done to improve the aforementioned dilem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…GERG-2008 is a wide-range noncubic EOS for NG components and is considered a standard reference equation suitable for natural gas applications. Recent literature studies compared GERG-2008 with other cubic and noncubic EOS to compute multicomponent SFE and concluded that GERG-2008 EOS gives better results. Hence, we selected GERG-2008 EOS for our process simulation.…”
Section: Fagru Simulationmentioning
confidence: 99%
“…GERG-2008 is a wide-range noncubic EOS for NG components and is considered a standard reference equation suitable for natural gas applications. Recent literature studies compared GERG-2008 with other cubic and noncubic EOS to compute multicomponent SFE and concluded that GERG-2008 EOS gives better results. Hence, we selected GERG-2008 EOS for our process simulation.…”
Section: Fagru Simulationmentioning
confidence: 99%
“…Besides the visual PVT cell, an automatic chilled mirror instrument is commonly used to measure the dew point of natural gases. , In this instrument, the gas is kept at constant pressure in a chamber that is equipped with a mirror. To measure the dew point, the backside of the mirror is cooled to detect the formation of liquid condensate on the mirror surface.…”
Section: Introductionmentioning
confidence: 99%